Education, language policy and language use in the Philippines - Symaco, L.P. (John Benjamins Publishing, 2017)
The roles of language policy and language practice and use in education have been regarded to influence the efficacy of teaching and learning in the school setting. With the rise of globalisation and internationalisation of services in education, the objective of producing manpower that is equipped to the demands of the knowledge- based economy has realigned government policies worldwide to put education at the forefront of its development plans. From the rise of English language as 'the' language for globalisation calls for a more inclusive and locally- oriented mother-tongue based multilingual education (MTB-MLE), this article will discuss broadly the dynamics of language, access and influence, and will look at the Philippines as a country case study of explicit and implicit declarations in language policy and use, as affecting the education sector, and access to the labour market.